Sexual Segregation in Iberian Noctule Bats - Ibáñez, Carlos; Guillén, Antonio; Agirre-Mendi, Pablo T.; Juste, Javier; Schreur, Godfried; Cordero, Ana I.; Popa-Lisseanu, Ana G. (Journal of Mammalogy, 2009)
Sexual segregation during the breeding season is common in many temperate bat species, and may be related to sex-specific thermoregulatory, microclimatic, or energetic requirements. We compiled capture data for 3 species of Nyctalus (noctule bats) obtained over .20 years to study reproductive and migratory strategies of these species in southwestern Europe. Within the Iberian Peninsula, several different strategies regarding sex distribution and migratory behavior were observed within each of the 3 Nyctalus species. In the northern part of Iberia there are populations of the 3 species composed of males all year-round with females appearing only during the mating season. Reproduction by females in this area has not been confirmed. In central and southern Iberia there are breeding populations in which sexual segregation occurs only at the roosts or at a regional scale, possibly with females located at lower elevations during the breeding season. Female-biased, long-distance migration is likely to be the cause of sexual segregation in populations of N. noctula and N. leisleri in northern and central Iberia, but not of N. lasiopterus, absent in central Europe. For this latter species, segregation by elevation also could occur in northern Iberia. The Iberian Peninsula is a good example of how breeding strategies and migratory behavior in bats can be very flexible and vary across relatively small geographical scales. Peer reviewed